2016
DOI: 10.4236/wjnse.2016.64013
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biofunctionalized Cellulose Acetate Nanoscaffolds for Heart Valve Tissue Engineering

Abstract: Currently-used mechanical and biological heart valve prostheses have a satisfactory short-term performance, but may exhibit several major drawbacks on the long-term. Mechanical prostheses, based on carbon, metallic and polymeric components, require permanent anticoagulation treatment, and their usage often leads to adverse reactions, e.g. thromboembolic complications and endocarditis. In recent years, there is a need for a heart valve prosthesis that can grow, repair and remodel. The concept of tissue engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…[25] It's well known that the native cotton fibers are used as conventional wound dressing materials since ancient times. [88] Cotton is used as a template for the biomaterials which are loaded with desirable features such as antimicrobial and nonadhesion properties as well as accelerated healing materials like glycogen, collagen, and gelatin. [25] The wound is multi diversity, cuttings, burns, ulcers, and diabetes in which each cellulosic biomaterial is suitable according to wound type.…”
Section: Wound Dressingmentioning
confidence: 99%
“…[25] It's well known that the native cotton fibers are used as conventional wound dressing materials since ancient times. [88] Cotton is used as a template for the biomaterials which are loaded with desirable features such as antimicrobial and nonadhesion properties as well as accelerated healing materials like glycogen, collagen, and gelatin. [25] The wound is multi diversity, cuttings, burns, ulcers, and diabetes in which each cellulosic biomaterial is suitable according to wound type.…”
Section: Wound Dressingmentioning
confidence: 99%
“…Interestingly, CA has also been proven as an effective material for tissue scaffold engineering, providing good mechanical stability, and ability to mimic the extracellular matrix for cell attachment, growth, and advanced formation of targeted tissues (e.g., bones and skin) [100]. Chainoglou et al has even demonstrated the possibilities of CA for heart valve tissue engineering, through a successful promotion of cardiac cell growth and proliferation [101]. Each one of these applications is dependent on their overall properties, which, in turn, are dependent on the polymer chemical characteristics, such as molar mass, molar mass distribution, DP, and degree of substitution (DS) [102].…”
Section: Cellulose Acetate (Ca)mentioning
confidence: 99%
“…Cellulose acetate (CA), perhaps the most commercially appealing ester derivative of cellulose, is characterized by fine molecular arrangement, low toxicity properties but poor structural stability, and mechanical strength [30]. CA can be cost-effectively processed into practical designs such as fibers, films, porous bulks, and most commonly for the synthesis of cost-effective asymmetric membranes [31]. CA’s long-established exercise in industry undermined its potential for advanced application and only recently surfaced as an auspicious material for tissue engineering substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun blends of CA were validated as remarkable wound dressing constituents with low-adherence and high healing support considering cell proliferation and collagen extracellular matrices deposition [32]. CA has been investigated for artificial blood vessels [33], skin grafts [34] and heart valve tissue engineering [31].…”
Section: Introductionmentioning
confidence: 99%